SAT0435 Knee Osteoarthritis and Periarticular Structure Quantified by Ultrasound. A Case-Control Study. (10th June 2014) - Nuñez, M.; Sastre, S.; Nuñez, E.; Saulό, A.; Segur, J.M.; Maurits, N.M.; Moreno, M.; Cabestany, J.; Segarra, J.; Segura, V.; Lozano, L.; Alemany, X.; et al.
Abstract : Background: Assessment of pain and physical function is complex in patients with knee osteoarthritis (OA), as standard criteria are lacking.A previous study examining correlations between functional capacity and pain (WOMAC) and anthropometric characteristics and periarticular knee structure (quantified by ultrasound imaging) in females with knee OA found increased quadriceps muscle density was associated with higher functional disability and pain scores, suggesting that not only joint wear and symptom severity are involved and more objective measures are necessary. Objectives: To determine and compare the periarticular knee structure in obese patients with knee OA and a healthy control group. Methods: Analytical case-control study. Study group. Patients diagnosed with knee OA. Control group . Adults with no history of knee involvement, able to walk normally, with no pain or functional difficulties on examination and no history of surgery in other lower limb joints. Controls were matched for age, sex and body mass index (BMI). Sociodemographic, clinical, functional (Timed Up and Go test [TUG]) and anthropometric (weight, height, BMI, waist circumference, and lower limb [suprapatellar and infrapatellar indices]) data were collected. Periarticular knee structure was assessed by ultrasound (thickness of subcutaneous fat [distance from skin to fascia, in mm] and quadriceps/rectus femoris [distance between fascia and femur, in mm]) and appearance [density on digital image analysis according to Maurits et al]). Statistical Analysis . Groups were compared using the t test for continuous variables and χ 2 test for categorical variables. Results: 66 lower limbs from 14 patients (mean age 62.7 [SD 8.6]) years, BMI 30.4 (SD 5.9) and 19 matched controls (mean age 62.6 [SD 8.1] years, BMI 30.1 [SD 4.7]) were evaluated. Comparison between groups: no significant differences in anthropometric measures were found. TUG took a mean 13.7s (6.7) and 9.9s (2.4) in patients and controls, respectively, p=0.002. Mean subcutaneous fat was 18.7 (SD 9.8) mm and 15.2 (4.41) in patients and controls, respectively, p=0.028. Mean quadriceps muscle density was 61.1 (25.9) and 41.7 (13.7), respectively, p=0.001. Conclusions: Between-group differences were found in the periarticular knee structure. Patients with knee OA had increased subcutaneous fat thickness and quadriceps muscle density was observed compared with controls. These findings suggest that the assessment of periarticular structures in these patients analyzed by digital image derived from ultrasound could add a variable to determine more objectively uniform methods in the classification of patients and evaluation of results. References: Maurits NM et al. Muscle ultrasound analysis: normal values and differentiation between myopathies and neuropathies. Ultrasound Med Biol 2003;29:215-25. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3136